Stable isotopes elucidate body-size and seasonal fluctuations in the feeding strategies of planktivorous fishes across a semi-enclosed tropical embayment - Skinner, Christina; Pei, Yu-De; Morimoto, Naoko; Miyajima, Toshihiro; Wyatt, Alex S. J. (Frontiers in Ecology and Evolution, 2022)
Reef fish may switch feeding strategies due to fluctuations in resource availability or through ontogeny. A number of studies have explored these trophodynamics using carbon (δ13C) and nitrogen (δ15N) stable isotopes, but additional tracers such as sulfur isotopes (δ34S) show strong potential in systems where δ13C and δ15N results are ambiguous. We tested the utility of adding δ34S to conventional δ13C and δ15N analysis to detect seasonal and body size changes in resource use of two planktivorous damselfish, Dascyllus reticulatus and D. trimaculatus across the Puerto Galera embayment in the Philippines. We analysed stable isotope ratios (δ13C, δ15N, and δ34S) in multiple fish tissues (liver, eye, muscle) to represent different dietary timeframes. We then compared fish tissue isotopes against particulate organic matter (POM: δ13C and δ15N) and POM suspension feeder (the tunicate Polycarpa aurata: δ13C, δ15N, and δ34S) across the same sites. There were size-based and seasonal differences in damselfish resource use, the latter of which were most pronounced in fast-turnover liver. Small fish (< 70 mm) demonstrated significant seasonality, appearing to switch their resource use between the rainy season and the dry season, while there was no seasonal variation in larger fish (>70 mm). This suggests that smaller fish across the embayment employ an opportunistic feeding strategy to take advantage of fluctuating resource availability, while larger fish exhibit more consistent resource use. Isotope ratios of tunicates and POM further confirmed strong seasonality in this system, and a lack of a spatial isotopic gradient. δ15N did not seem to contribute to consumer resource use patterns, while by contrast, δ34S fluctuated significantly between sampling periods and was crucial for demonstrating seasonality in resource use. We recommend including δ34S when attempting to disentangle seasonal differences in resource use in aquatic food webs using stable isotopes.